2012
DOI: 10.1051/0004-6361/201118181
|View full text |Cite
|
Sign up to set email alerts
|

Jet-driving protostars identified from infrared observations of the Carina Nebula complex

Abstract: Aims. Jets are excellent signposts for very young embedded protostars, so we want to identify jet-driving protostars as a tracer of the currently forming generation of stars in the Carina Nebula, which is one of the most massive galactic star-forming regions and which is characterised by particularly high levels of massive-star feedback on the surrounding clouds. Methods. We used archive data to construct large ( > ∼ 2 • × 2 • ) Spitzer IRAC mosaics of the Carina Nebula and performed a spatially complete searc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 32 publications
(72 reference statements)
1
51
1
Order By: Relevance
“…Several studies of the youngest stellar populations in the CNC concluded that the currently ongoing star formation process is, to a large degree, spatially restricted to the edges and surfaces of irradiated clouds, e.g., the tips of the numerous pillars (Smith et al 2010;Ohlendorf et al 2012;Gaczkowski et al 2013). This suggests a causal connection between the star formation process and local cloud compression.…”
Section: Total Fir Luminositymentioning
confidence: 99%
“…Several studies of the youngest stellar populations in the CNC concluded that the currently ongoing star formation process is, to a large degree, spatially restricted to the edges and surfaces of irradiated clouds, e.g., the tips of the numerous pillars (Smith et al 2010;Ohlendorf et al 2012;Gaczkowski et al 2013). This suggests a causal connection between the star formation process and local cloud compression.…”
Section: Total Fir Luminositymentioning
confidence: 99%
“…The Herschel fluxes have been used in our recent study of the infrared detected jet-driving protostars in the Carina Nebula (Ohlendorf et al 2012). In forthcoming publications we will report results about the detailed small-scale structure of the clouds, the numerous point-like FIR sources (most of which are expected to be embedded protostars), as well as the relation between the CNC and the Gum 31 nebula.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…1, the Spitzer IRAC maps cover ≈87% of the area of our Herschel maps. We performed point source detection and photometry in these IRAC mosaics, using the Astronomical Point source EXtractor (APEX) module of the MOsaicker and Point source EXtractor package (MOPEX; Makovoz & Marleau 2005), as described in Ohlendorf et al (2012a).…”
Section: Spitzer Irac Datamentioning
confidence: 99%
“…Furthermore, 40 Herbig-Haro jets have been discovered by Smith et al (2010a) through a deep Hubble Space Telescope (HST) Hα imaging survey. The driving sources of many of these jets were recently revealed and analyzed by Ohlendorf et al (2012a). Povich et al (2011) published a catalog of 1439 YSO candidates (PCYC catalog) based on mid-infrared excess emission detected in the Spitzer data.…”
Section: Introductionmentioning
confidence: 99%